2022
DOI: 10.3390/cancers14194718
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Governs β-Estradiol-ERα-Involved Endometrial Tumorigenesis via Inhibition of STING Transcription

Abstract: Purpose: The stimulator of interferon genes (STING) pathway plays a crucial role in antitumor immunity, and it is strictly regulated by many types of post-translational modifications. However, the contribution of acetylation involved in the regulation of STING to endometrial tumorigenesis remains unclear. Methods: We attempted to identify the key role of STING in endometrial carcinoma (EC) tissue and cell lines and explore its epigenetic regulation mechanism by HDACs that are critically involved in EC. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…86,87 Consequently, there is reason to believe that both HDAC2 and HDAC3 expression is reduced as endometriotic lesions become more fibrotic, especially in DE lesions as reported here, in particular given the report that both HDAC2 and HDAC3 are constitutively expressed in normal endometrium. 88 This may also be supported by the report that HDAC3 overexpression in conjunction with estrogen-ERα suppresses STING endometrial epithelial cells 89 yet STING is upregulated in ectopic endometrium. 90 Indeed, we found that culturing an endometrial epithelial cell line in high-stiff substrates resulted in downregulation of HDAC3, 91 which may account for reduced endometrial HDAC3 expression in infertile women with endometriosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…86,87 Consequently, there is reason to believe that both HDAC2 and HDAC3 expression is reduced as endometriotic lesions become more fibrotic, especially in DE lesions as reported here, in particular given the report that both HDAC2 and HDAC3 are constitutively expressed in normal endometrium. 88 This may also be supported by the report that HDAC3 overexpression in conjunction with estrogen-ERα suppresses STING endometrial epithelial cells 89 yet STING is upregulated in ectopic endometrium. 90 Indeed, we found that culturing an endometrial epithelial cell line in high-stiff substrates resulted in downregulation of HDAC3, 91 which may account for reduced endometrial HDAC3 expression in infertile women with endometriosis.…”
Section: Discussionmentioning
confidence: 79%
“… 86 , 87 Consequently, there is reason to believe that both HDAC2 and HDAC3 expression is reduced as endometriotic lesions become more fibrotic, especially in DE lesions as reported here, in particular given the report that both HDAC2 and HDAC3 are constitutively expressed in normal endometrium. 88 This may also be supported by the report that HDAC3 overexpression in conjunction with estrogen‐ERα suppresses STING endometrial epithelial cells 89 yet STING is upregulated in ectopic endometrium. 90 …”
Section: Discussionmentioning
confidence: 79%
“…In endometrial cancer, histone deacetylase HDAC3 interacts with β-estradiol-ERα and induces histone 3 lysine 4 deacetylation at the STING promoter, thus decreasing STING expression. Inhibiting HDAC3 increases STING expression and suppresses tumorigenesis 114 . A recent study has reported that protein arginine methyltransferase PRMT1 methylates cGAS at a conserved R133 residue, prevents cGAS dimerization, and inhibits cGAS/STING signaling in cancer cells.…”
Section: Strategies For Harnessing the Cgas-sting Pathway In Cancer T...mentioning
confidence: 99%
“… 11 Many of these ISGs encode proteins with antiviral properties, 12 , 13 with some acting back on STING to further amplify its responses. 14 The molecules are thought to involve positive feedback regulation via STAT1 promoter binding, 14 ubiquitination, 15 sumoylation, 16 phosphorylation, 17 methylation, 18 or 19 acetylation of cGAS or STING itself.…”
Section: Introductionmentioning
confidence: 99%